Strategi Promosi Wisata Melalui Push Notification Smart Tourism Berbasis PWA di Pemandian Teluk Sibayan - Iqbal, Muhammad; Rohminatin, Rohminatin; Syahputra, Abdul Karim; Indriani, Meliya; Khairani, Alya Fauza (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
The "CITRA" Hot Spring in Teluk Sibayan, Batu Bara Regency, North Sumatra, holds significant potential as a tourist destination. However, the main challenges faced by the management include a lack of digital promotion, limited tourist visits from outside the region, and a shortage of human resources skilled in using information and communication technology (ICT). The community service project by the STMIK Royal Faculty aimed to address these issues through mentoring, training, and technology development. The methods employed included workshops and training on digital tourism promotion, the creation of a web-based ticketing application, and a smart tourism application based on Progressive Web Apps (PWA) with push-notification features. Additionally, social media accounts on Instagram and Facebook (@sibayan.pemandian) were established as online promotion platforms. The results of this initiative indicate an improvement in the staff’s capacity to utilize technology, along with the provision of digital systems that streamline visitor management and promotion efforts. As a result, Pemandian Citra now has stronger digital infrastructure to support tourism promotion and attract more visitors.Keywords: community service; hot springs; PWA; smart tourism; promotion Abstrak: Pemandian Air Panas "CITRA" di Teluk Sibayan, Kabupaten Batu Bara, Sumatera Utara, memiliki potensi besar sebagai destinasi wisata. Namun, permasalahan utama yang dihadapi pengelola adalah kurangnya promosi digital, minimnya kunjungan wisatawan dari luar daerah, serta keterbatasan sumber daya manusia dalam menggunakan teknologi informasi dan komunikasi (TIK). Kegiatan pengabdian masyarakat oleh Tim Dosen STMIK Royal bertujuan untuk mengatasi masalah ini melalui pendampingan, pelatihan, dan pengembangan teknologi. Metode yang digunakan mencakup workshop dan pelatihan terkait promosi wisata digital, pembuatan aplikasi tiket berbasis web, serta aplikasi smart tourism berbasis Progressive Web Apps (PWA) dengan fitur push-notification. Selain itu, akun media sosial Instagram dan Facebook dengan nama pengguna @sibayan.pemandian juga dibuat sebagai sarana promosi online. Hasil dari kegiatan ini menunjukkan peningkatan kapasitas staf pemandian dalam memanfaatkan teknologi, serta penyediaan sistem digital yang mempermudah pengelolaan kunjungan dan promosi. Dampaknya, Pemandian Citra kini memiliki infrastruktur digital yang lebih kuat untuk mendukung promosi wisata dan meningkatkan daya tarik bagi wisatawan..Kata kunci:  Pengabdian Masyarakat; Pemandian Air Panas; PWA; Smart Tourism; Promosi